Peningkatan Literasi Ekonomi Syariah pada Siswa/i MA Ar-Rosyidiyah Sungai Alam Kabupaten Bengkalis - Muhamamd Ashsubli; Dewi Oktaviani (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Sharia economic literacy is an important aspect in shaping economic understanding and behavior that align with Islamic values among the younger generation. However, the level of students’ understanding of sharia economic concepts in madrasahs remains relatively low and has not been optimally integrated into daily life. This study aims to enhance and analyze sharia economic literacy among students of Madrasah Aliyah Ar-Rosyidiyah, Sungai Alam Village, Bengkalis Regency. The research employed a qualitative approach with data collection techniques including direct field observation, in-depth interviews with teachers and students, and documentation of learning activities. The findings indicate that the improvement of sharia economic literacy can be achieved through strengthening learning materials, applying contextual approaches relevant to students’ daily lives, and increasing active teacher involvement in linking sharia economic concepts with everyday economic practices. Field observations also revealed changes in students’ understanding of fundamental sharia economic principles such as justice, the prohibition of usury (riba), and the concept of muamalah. This study is expected to serve as a reference for Islamic educational institutions in developing more effective and sustainable sharia economic learning strategies